Fluoro-Modulated Molecular Geometry in Diketopyrrolopyrrole-Based Low-Bandgap Copolymers for Tuning the Photovoltaic Performance - Zhang, Cai'e; Liu, Yahui; Tu, Jia; Ming, Shouli; Xu, Xinjun; Bo, Zhishan (Frontiers in Chemistry, 2019)
Fluorination of conjugated polymers is an effective strategy to tune the energy levels for obtaining high power conversion efficiency (PCE) in organic solar cells. In this work, we have developed fluoro-modulated molecular geometries in diketopyrrolopyrrole based low-bandgap copolymers. In these polymers, planar conformation can be locked by intramolecular noncovalent interaction (intramolecular supramolecular interaction) between the sulfur atoms and the introduced F atoms (F···S interaction). By varying the fluorinated moieties, such a planarity can be disturbed and the molecular geometry is tuned. As a result, the polymer’ properties can be modulated, including the ultraviolet-visible absorption spectrum to become broaden, charge mobility to be enhanced, open-circuit voltage (Voc) and short-circuited current (Jsc) to be elevated, and thus photovoltaic performance to be improved. The photovoltaic device based on PCFB, one of the fluorinated terpolymers, exhibited a high PCE near 8.5% with simultaneously enhanced Voc and Jsc relative to the nonfluorinated one (PCB).